PENGARUH MEDITASI MINDFULNESS DALAM MENEKAN KENAKALAN REMAJA - gusti ayu suryani (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2023)
Teenagers experience a period of transition from childhood to adulthood, it can be said a period of searching for identity. At this time teenagers often take aggressive actions such as bullying behavior, consuming illegal drugs, and often behaving that poses a risk to society. These behaviors can be revented through a mindfulness meditation approach, which can be done by sitting comfortably, quietly and focusing on the object of mental awareness and can be done through the process of breathing, chanting a mantra or statement of visualization of appreciation and then consciously examining the mind openly. Through this mindfulness meditation routinely, teenagers will be able to maintain emotional stability, always positively accept themselves as they are and be able to face life more calmly.